Electroacupuncture combined with cognitive rehabilitation outperforms cognitive rehabilitation alone in treating post-stroke cognitive impairment: a randomized controlled trial - Yisha Guo; Tingting Sun; Fengxi Qiu; Xueyi Li; Weiwei Cui; Zhenhua Liao; Jiajia Yao (Frontiers in Neurology, 2025)
This study aimed to evaluate the effects of a 12-week intervention combining electroacupuncture (EA) with conventional cognitive rehabilitation (CR) on cognitive recovery and brain network topological properties in stroke patients. Thirty-four post-stroke cognitive impairment (PSCI) patients were randomly assigned to either an EA + CR group or a CR-only group, with both undergoing five weekly interventions for 12 weeks. Cognitive assessments and Diffusion Tensor Imaging tests were performed pre- and post-intervention. Primary outcomes included the Montreal Cognitive Assessment (MoCA), Digit Span Test (DST), Auditory Verbal Learning Test (AVLT-H), and Aphasia Screening Scale. Secondary outcomes measured brain network global and nodal properties. The EA + CR group showed significant improvements in MoCA (p < 0.001), AVLT-H (p = 0.004), and in areas like naming (p = 0.022), attention (p < 0.001), and delayed recall (p < 0.001). Local brain network metrics, such as clustering coefficients (Cp) and local efficiency (Eloc), were significantly higher (p < 0.05) in the EA + CR group, though global efficiency (Eglob) was unchanged. Improvements in Eloc were positively correlated with MoCA scores (r = 0.0716, p = 0.018). Specific brain regions, including the medial and paracentral cingulate gyrus, inferior temporal gyrus, and left supramarginal gyrus, exhibited significant nodal property differences, suggesting that EA may enhance cognitive recovery by targeting cognitively relevant regions. These findings indicate that EA, combined with CR, is a safe and effective treatment for cognitive impairment following stroke, potentially via structural brain network improvements.Clinical trial registrationhttps://clinicaltrials.gov/, ChiCTR2200066160.